From Secularism to Islamism: A Portrait of Minority Dynamics in Turkey's Changing Political Landscape - Azhari, Doni (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This study examines the evolving dynamics of minority groups within Turkey's shifting political landscape, from Atatürk's secular reforms to the rise of Islamist ideology under Erdoğan's leadership. It traces Turkey's political transformation from the decline of the Ottoman Empire through the establishment of a secular republic and the recent resurgence of Islamic influence in governance. The research employs qualitative methods, including historical analysis and case studies, to explore how these political shifts have impacted minority rights, cultural expressions, and societal integration. Findings reveal that both secularization and Islamization processes have presented challenges for minority communities, albeit in different ways. The study highlights the ongoing tension between modernization, traditional values, and religious identity in shaping Turkey's national character and its treatment of minority groups. This research contributes to broader discussions on the role of religion in public life, the limits of secularism, and the complexities of managing diversity in modern nation-states.